Unveiling the Mediating Role of Emotions and Engagement in Celebrity Endorsement and Purchase Intention - Anggun, Nita Putri; Setyawan, Anton Agus; Saputro, Edy Purwo; Kussudyarsana, Kussudyarsana (Almana : Jurnal Manajemen dan Bisnis, 2025)
Research on purchase intention in the digital era shows inconsistent findings regarding the impact of celebrity endorsement, with some studies highlighting its influence while others emphasize the stronger role of psychological factors. This study aims to examine the effect of celebrity endorsement on purchase intention by positioning emotional attachment and customer engagement as mediating variables. A quantitative approach was used with 200 followers of Somethinc’s official social media account as respondents. Data were analyzed using PLS-SEM with SmartPLS 3.0. The results reveal that celebrity endorsement has a significant positive influence on purchase intention. Furthermore, celebrity endorsement enhances emotional attachment and customer engagement, both of which strengthen consumers’ intention to purchase. Mediation analyses confirm that emotional attachment and customer engagement play important roles in bridging the relationship between celebrity endorsement and purchase intention. In conclusion, the study demonstrates that celebrity endorsement is most effective when supported by strategies that foster emotional closeness and active engagement, offering valuable insights for digital marketing practices in the skincare and cosmetics industry.